Enhancing Listening Comprehension through a Group Work Guessing Game - Sasan Baleghizadeh; Fatemeh Arabtabar (Asociación Colombiana de Profesores de Ingles, 2010)
The present paper is an attempt to introduce an innovative technique for a more effective teaching of L2 listening comprehension through a process-oriented approach. Much of what is traditionally known as listening practice is in fact testing material in which students are required to listen to a recording and answer a number of comprehension questions. However, as a preliminary step, teachers should focus on the process of listening comprehension by encouraging students to employ efficient learning strategies during the listening process and cooperatively evaluate them in the class. The suggested technique in this article provides students with appropriate metacognitive strategies, which pave the way for successful L2 listening practice.